A 3D Printer in the Lab: Not Only a Toy. Issue 27 (13th July 2022) - Saggiomo, Vittorio
Abstract: Although 3D printers are becoming more common in households, they are still under‐represented in many laboratories worldwide and regarded as toys rather than as laboratory equipment. This short review wants to change this conservative point of view. This mini‐review focuses on fused deposition modeling printers and what happens after acquiring your first 3D printer. In short, these printers melt plastic filament and deposit it layer by layer to create the final object. They are getting cheaper and easier to use, and nowadays it is not difficult to find good 3D printers for less than €500. At such a price, a 3D printer is one, if not the most, versatile piece of equipment you can have in a laboratory. Abstract : A short review on the multiple applications of consumer 3D printers in a laboratory setting. From simple downloading and printing to 3D design to making specialized 3D printing material to reprogramming the 3D printer as a robot to automate laboratory procedures.